Did AI Just Roast Me?Understanding How Students Feel About AI Feedback - Marwa Aulianissa; Salsabilla; Nana Priajana (Indonesian Journal of Educational Technology, 2026)
Feedback plays a critical role in helping EFL students improve the quality of their writing. As AI writing tools increasingly provide immediate and personalized feedback, students now receive feedback from lecturers, peers, and AI tools. This study aims to examine EFL students' perceptions of AI-generated feedback, focusing on awareness, meaning-making, perceived learning support, engagement, autonomy, reflection, and ethical concerns in academic writing. A quantitative descriptive design with a cross-sectional survey approach was employed. Fifty undergraduate students in the English Language Teaching Department at UIN Siber Syekh Nurjati Cirebon participated in this study. Data were collected through a Google Forms questionnaire consisting of demographic questions and 15 Likert-scale statements, and were analyzed using frequency distributions, total scores, and index scores categorized into low, medium, and high levels. The findings show that students can identify AI feedback (index = 79.5, high), perceive AI feedback as objective (77.5, high), consider ethics in AI use (81.5, high), and express strong concern about plagiarism (90, high). However, confidence after using AI feedback (71.5), perceived accuracy (72.5), and prior knowledge in interpreting feedback (69) remain in the medium category. These results suggest that AI feedback supports writing confidence and autonomous learning, but students still need lecturer guidance to avoid overreliance and to strengthen critical interpretation of automated feedback.